2017
DOI: 10.1111/opn.12181
|View full text |Cite
|
Sign up to set email alerts
|

Testing an app for reporting health concerns—Experiences from older people and home care nurses

Abstract: The use of an app should be considered as a useful information and communication technology innovation that can improve communication and accessibility for older people with home-based health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(106 citation statements)
references
References 37 publications
(48 reference statements)
2
95
0
Order By: Relevance
“…The older persons had experienced the app's functions associated with regular self-reporting of health concerns monitored by the homecare nurses and appreciated the access to relevant self-care advice. This is in line with other studies that show self-care skills can be improved with the use of a mobile phone as a tool (9,11) or be seen as good support (28). In other populations, versions of the app were developed for use by persons with pancreatic or prostate cancer.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The older persons had experienced the app's functions associated with regular self-reporting of health concerns monitored by the homecare nurses and appreciated the access to relevant self-care advice. This is in line with other studies that show self-care skills can be improved with the use of a mobile phone as a tool (9,11) or be seen as good support (28). In other populations, versions of the app were developed for use by persons with pancreatic or prostate cancer.…”
Section: Discussionsupporting
confidence: 86%
“…This quasi-experimental study is a part of the development and optimisation phase that focuses on the outcomes of the intervention before conducting an evaluation in a randomised controlled study (RCT). Other parts of the intervention have been published elsewhere (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent surveys point to growth in Internet use by older adults, and studies indicate that age becomes less important if tools are easy to use and training and support is provided when introducing new technologies (Anderson & Perrin, 2017;Göransson et al, 2018;Østensen, Gjevjon, Øderud, & Moen, 2017;Vaportzis, Giatsi Clausen, & Gow, 2017). In this study, a majority of informants reported to use the app regularly for 8 weeks to register their food and beverage consumption.…”
Section: Discussionmentioning
confidence: 74%
“…Study results in this category are much less positive than in other technology categories. Only three of the ten studies yielded positive results, all of which are situated in outpatient long-term care [50][51][52]. In contrast to these, there are three studies without any signi cant positive effects [53][54][55], and four studies with ambivalent results [56][57][58][59].…”
Section: Telecarementioning
confidence: 99%